Virus Detection of Pacific White Shrimp (Litopenaeus vannamei) at Fish Quarantine Center, Quality Control, and Security of Fishery Product in Surabaya I - Aulia Azizah; Darmawan Setia Budi; Arif Habib Fasya; Muhammad Hanif Azhar; Hapsari Kenconojati (Airlangga University, 2019)
Pacific white shrimp (Litopenaeus vannamei) is one of the leading fisheries commodities that have important economic value and are in great demand by consumers in the market. Pacific white shrimp has several advantages, namely rapid growth, able to adapt to a high range of salinity, and can be cultured with a super intensive system, but in recent years the total shrimp production in Indonesia has decreased. In 2012 the total shrimp production decreased from 1.900 tons to 1.025 tons, the virus is thought to be a pathogen that triggers disease in shrimp and causes high mortality. The type of virus that causes disease in pacific white shrimp cultivation is Taura Syndrome Virus (TSV), Infectious Myonecrosis Virus (IMNV), and White Spot Syndrome Virus (WSSV). The purpose of this study is to detect viruses that infected and determine the prevalence of viruses that attack pacific white shrimp. The research was conducted in December 2018 to January 2019 at Fish Quarantine Center, Quality Control and Security of Fishery Product Surabaya I. The material used in the study was 37 post larval samples. Samples extracted using Silica Extraction Kit, then detected molecularly using PCR (Polymerase Chain Reaction). This research was observational, then the data obtained were analyzed descriptively. The results showed that there were 3 positive samples of IMNV and 2 positive samples of WSSV with prevalence values of 8.10% and 5.40%. High and low prevalence values are influenced by the level of virus spread and inappropriate environmental conditions. Keywords : Pacific white shrimp, PCR (Polymerase Chain Reaction), prevalence, virus.